Ethnic and migration components of social practices: opportunities to regain trust - Irina A. Ostapenko, Irina V. Glushko, Irina M. Lavrukhina, Tatyana M. Zueva, (Opción, 2019)
The research objective is to reveal the influence of migration processes on interethnic relations and opportunities for achieving civil peace and inter-ethnic stability in multinational states. The leading method is analysis and generalization of sociological data. As a result, the attributes of a common citizens’ identity – the common state, the common history and territory, language and culture – have the consolidating potential in the respondents’ opinion. In conclusion, the creation of effective mechanisms for withdrawal of inter-ethnic tensions and for increasing confidence in the authorities presupposes painstaking work and consists of activities that may seem small in terms of Big Politics.